Edukasi Interprofessional Education and Collaboration (IPEC) pada Tenaga Kesehatan Puskesmas - Siti Munawaroh; Eti Poncorini Pamungkasari; Veronika Ika Budiastuti; Yunia Hastami; Atik Maftuhah; Bulan Kakanita Hermasari; Dian Nugroho; Aldira Ayu Nastiti Nur Hanifah; Afifah Nurul Izzah (Abdimas Universal, 2024)
Collaboration in health services is an important thing to implement. With good collaboration, we can provide quality services and support patient health and comfort. Without good collaboration between health workers, medical errors can result. One of the obstacles faced by clinical supervisors in the field is that they have not received education related to IPEC when they study. So they have difficulty teaching IPEC. Therefore, training is needed regarding the implementation of IPEC for health workers in educational facilities such as community health centers. This community service aims to conduct IPEC training for health workers at the Karangdowo health center, Klaten. Service activities begin with socialization about IPEC, followed by assessing perceptions regarding interprofessional collaboration from health workers using the ISVS (Interprofessional Socialization and Valuing Scale) – 9A questionnaire. The service was attended by 30 participants from various health professions at the Puskesmas. The results of the assessment of perceptions of interprofessional collaboration obtained a scale score of 4-7 (medium-very large) indicating that the perception of health workers at the Karangdowo Health Center is good.. IPEC counseling plays an important role in increasing collaboration capabilities between health workers at Community Health Centers.